2022
DOI: 10.1038/s41467-022-32485-9
|View full text |Cite|
|
Sign up to set email alerts
|

Generation of a CRISPR activation mouse that enables modelling of aggressive lymphoma and interrogation of venetoclax resistance

Abstract: CRISPR technologies have advanced cancer modelling in mice, but CRISPR activation (CRISPRa) methods have not been exploited in this context. We establish a CRISPRa mouse (dCas9a-SAMKI) for inducing gene expression in vivo and in vitro. Using dCas9a-SAMKI primary lymphocytes, we induce B cell restricted genes in T cells and vice versa, demonstrating the power of this system. There are limited models of aggressive double hit lymphoma. Therefore, we transactivate pro-survival BCL-2 in Eµ-MycT/+;dCas9a-SAMKI/+ hae… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 73 publications
(81 reference statements)
0
10
0
Order By: Relevance
“…Resistance to BH3-mimetic drugs is a critical and emerging issue which threatens to limit the benefit of this class of anti-cancer therapy. While genetic changes underlying resistance to the BCL-2 inhibitor venetoclax are beginning to be uncovered [5,23,26,[35][36][37][38][39], less attention has been focused on resistance to MCL-1 inhibitors, which have entered clinical trials for diverse haematological malignancies [5]. To this end, we sought to identify factors that could confer resistance to MCL-1 inhibitors using murine and human models of highly aggressive, MYC-driven lymphoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resistance to BH3-mimetic drugs is a critical and emerging issue which threatens to limit the benefit of this class of anti-cancer therapy. While genetic changes underlying resistance to the BCL-2 inhibitor venetoclax are beginning to be uncovered [5,23,26,[35][36][37][38][39], less attention has been focused on resistance to MCL-1 inhibitors, which have entered clinical trials for diverse haematological malignancies [5]. To this end, we sought to identify factors that could confer resistance to MCL-1 inhibitors using murine and human models of highly aggressive, MYC-driven lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…The second major mechanism driving resistance we identified in our S63845-resistant cells was upregulation of the pro-survival proteins BCL-XL and A1. Many studies have reported the over-expression of pro-survival BCL-2 proteins as resistance factors for venetoclax therapy, including in patient samples and in in vitro whole genome CRISPR/Cas9 screens [ 35 , 37 , 39 , 52 , 53 ]. In our study, Eµ-Myc lymphoma cells that had achieved resistance to S63845 through upregulation of BCL-XL and A1 also showed resistance to etoposide treatment due to the over-expression of these pro-survival proteins preventing apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…A frequent mechanism of resistance in malignant cells to loss/inhibition of BCL-2 pro-survival proteins by BH3-mimetic drugs is the upregulation of one/several of the non-targeted pro-survival BCL-2 family proteins [ 16 , 30 ]. If BCL-W is required to support the ongoing survival of lymphoma cells, it is possible that such compensatory changes could occur to allow MYC-driven lymphomagenesis in the absence of BCL-W. To investigate this, we performed Western blot analyses on tumour tissues from Eµ-Myc T/+ ;Bcl-w +/+ and Eµ-Myc T/+ ;Bcl-w −/− mice ( n = 12 per genotype; n (females) = 15, n (males) = 9) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, in various solid cancers, BCL-W has been detected as a potential resistance factor [ 39 ], and is upregulated in a host of these malignancies [ 40 ], but to our knowledge this is not the case in haematological cancers. We recently published the results of a CRISPR activation (CRISPRa) screen in a murine model of double-hit lymphoma (DHL), where we identified resistance factors to Venetoclax treatment [ 30 ]. Interestingly, in this screen we identified upregulation of genes expressing the pro-survival BCL-2 family members BCL-XL, MCL-1, and A1 as factors that promoted DHL resistance to Venetoclax, but not BCL-W.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance of MCF-7 breast cancer cells to palbociclib is linked to stimulation of cyclin E/CDK2 and Myc activity, as evidenced by CRISPRa experiments [194]. Another CRISPRa screen performed in BCL-2-expressing Eµ-Myc/dCas9a-SAM Kl/+ /sgBcl-2 lymphoma cells showed the BCL-2-related A1 protein to be associated to resistance to venetoclax [195]. A CRISPRa screening approach was also applied to activate expression of lncRNAs in order to identify putative players with a role in vemurafenib resistance in A375 melanoma cells, and loci potentially involved have been uncovered [196].…”
Section: Crispr Interference (Crispri) and Crispr Activation (Crispra...mentioning
confidence: 99%